Performance of Solar-powered Ejector Refrigeration System with Double-partitioned Water Storage Tanks (Zhileng xuebao)
A solar-powered ejector refrigeration system with double-partitioned water storage tanks was proposed and analyzed. The stratified water tank had higher energy storage capacity and better thermal stratification than the conventional design. The advantages of a partitioned water storage tank and large and small water tanks were fully utilized in the novel system to compensate for the disadvantages of low solar energy utilization and low solar-powered ejector refrigeration efficiency, which resulted from the solar energy instability. In this study, the performance of the novel system was analyzed using an hourly cooling load analysis method. The high-grade energy consumption of the novel system is approximately 1/5 that of the conventional mechanical compression refrigeration cycle. The whole-day working time increases by 4 hours and the cooling capacity increases by 36.8% compared with the solar-powered ejector refrigeration cycle for the conventional water tank. In addition, the hourly cooling capacity of the novel system and the hourly cooling load of the office are more consistent than those of the conventional system.